Professional Performance Strategy for Educators - Mujiono, *Mus; Amin, Alfauzan; Rizal, Imam (Universitas Syiah Kuala, 2022)
This study aims to determine the strategy of developing the professionalism of educators, this research is a qualitative descriptive study that tries to explore the meaning of educator professionalism as a step to develop the quality of madrasas by adjusting educational goals. In this study, the teacher sees the teacher as a key or central figure in the implementation of education or improving the quality of madrasa education, which has a very strategic position for all educational reform efforts that are oriented towards achieving the quality of students and schools. This is because, in this era of increasingly massive and extensive globalization, without the support of quality human resources (HR), a country will be left far behind. The benchmark for the development of Human Resources is a very urgent priority in the formation of personality for each country. In the face of social, economic, technological, and humanitarian competition, which is increasingly escalating massively, the requirements for the ability needed by people to do work are increasing, starting from knowledge, skills, and attitudes. From here, the demand for professionalism in working for an educator is needed to spur the success of their students. No matter how good the curriculum is designed by experts with the availability of adequate equipment and costs in accordance with education, in the end the success of professional education lies in the hands of the teacher